AN ANALYSIS OF DEPRESSION ON THE MAIN CHARACTER KYLE KINGSON ON THE BEASTLY FILM - Widyawati, Wiwin (Kodifikasia, 2014)
Abstract:This research is a literary criticism which uses psychological approach. It employs a literary criticism because the writer conducts discussion of literary works which is related with the personality of the main character in the Beastly film namely Kyle Kingson. The findings showed that there are five symptoms of depression from the main character Kyle Kingson namely, (1) feeling sad or unhappy, (2) loss of interest or pleasure daily activity that be loved before, (3) easy to be angry or easy to be offended, (4) difficult to take decision, less to concentrate, (5) feeling worthless, guilty and always thinking about past failures. Moreover, Kyle can solve his depression by himself and Zola and Will make Kyle confidence with his ugly face.Keywords: symptoms of depression, character, beastly film